Circular RNA hsa_circ_0000073 Enhances Osteosarcoma Cells Malignant Behavior by Sponging miR-1252-5p and Modulating CCNE2 and MDM2 - Ren, Zhijing; Yang, Qinqin; Guo, Jiajia; Huang, Haifeng; Li, Bo; Yang, Zhen; Tian, Xiaobin (Frontiers in Cell and Developmental Biology, 2021)
Objective: An increasing number of studies have demonstrated that circRNAs are involved in tumor progression. However, the role of hsa_circ_0000073 in Osteosarcoma (OS) is still not fully elucidated. Methods: qRT-PCR or Western blot was used to detect the gene expression. GeneChip analysis, Bioinformatics, Luciferase reporter and RIP assays were adopted to predict and verify the relationships between genes. Counting Kit-8 Assay, Clone Formation Assay, Wound-healing assay, Transwell assays, Cell cycle assays and in vivo tumorigenesis were employed to evaluate cell function. Results: Hsa_circ_0000073 was highly expressed in OS cell lines and could promote OS progression，including proliferation，migration, invasion and cell cycle in vitro as well as tumorigenesis in vivo. Mechanically, hsa_circ_0000073 could readily downregulate the expression of CCNE2 and MDM2 through miR-1252-5p, a tumor suppressor of OS cells identified further. Rescue experiments validated miR-1252-5p mimics or CCNE2/MDM2 shRNA could reverse the hsa_circ_0000073 overexpressing-induced impairment of malignant tumor behavior. Conclusion: hsa_circ_0000073 functions as a tumor promoter in OS to increase malignant tumor behavior through sponging miR-1252-5p and regulating CCNE2 and MDM2 expression, which could be a novel target for OS therapy.